Female Genital Mutilation (FGM) in Indonesia: Systematic Review - Rafidha Nur Alifah; Alfiana Ainun Nisa; Efa Nugroho; Dwi Yunanto Hermawan (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Indonesia is the third largest country that carries out female circumcision. As many as 51.2% of girls aged 0-11 years have undergone female circumcision. Female Genital Mutilation (FGM) or female circumcision is a dangerous traditional practice that still occurs in Indonesia, which has caused pros and cons among the community even though, based on scientific studies, female circumcision has been proven to have no health benefits. Female circumcision has even been banned by law and opposed by international health organizations. Objective: The study aims to identify factors influencing female circumcision in Indonesia, focusing on the Social Determinant and Health theory. Method: This study is a systematic review that collects several studies according to the PRISMA guidelines. Using relevant keywords, studies were obtained from various databases, such as Garuda, Google Scholar, and Semantic Scholar. Studies were collected from June to July 2024. Result: From 2.254 articles found, ten articles were selected for further analysis. Factors such as maternal age, maternal education, knowledge, culture/tradition, beliefs, family support, and sources of information also influence the practice of circumcision in female children. Conclusion: Female circumcision is a dangerous traditional practice that is still carried out today due to the culture and beliefs of the local community, which are still strong and believe that female circumcision must be carried out on their daughters.